Ghana Accountability For Learning Outcomes Projects (Galop) and its Impact On Academic Progression In Abuakwa North Municipality - Williams, Brobbey; Egyir-Mensah, Robert; Dokua, Felicia Nkansah; Asiedu, Isaac (Journal of Telematics and Informatics, 2025)
This study assesses Ghana's Accountability for Learning Outcomes Project (GALOP) role in students' academic progress in Abuakwa North Municipality. The respondents of this research are the GALOP teachers from nineteen (19) GALOP schools totalling 140 teachers. But the responding rate was 120 teachers. The study employed census sampling methods, and a questionnaire to gather information from respondents. A quantitative research approach was adopted using a descriptive cross-sectional design. The main analytical tools used in the study include frequency, distribution, percentages and linear regression. The findings revealed that GALOP positively impacted the quality of education in low-performing basic education schools. Again, GALOP was found to significantly predict learners' academic progression, indicating that the model (GALOP) activities explained 14.2% of the variance in learners' academic progress. Based on these results, it is recommended that teachers should be given adequate teachers professional development programs to enhance their abilities and improve their teaching competencies, which will enable them to implement the GALOP activities effectively. Effective implementation of GALOP positively impacts the learners’ academic progress. The study further recommends that GES should always give incentives or motivation to teachers to attract effective teaching.